Nuevos datos sobre el género Tulostoma (Gasteromycetes) en España, III - Martín Esteban, María Paz; Calonge, Francisco de Diego (Revista Catalana de Micologia, 2007)
New data all the Spanish species ol Tulostonta (Gasteromycetes ) III. Seven species of Tulostoma are studied here. New data on the chorology of T. Giovanellae Bres., T. Kotlabae Pouzar, T. Lloydii Bres. and T. nanum (Patouillard) J. E . Wright are also added.